ANALISIS SEMIOTIKA JOHN FIESKE TENTANG MASKULINITAS DALAM FILM MIRACLE IN CELL NO 7 KARYA LEE HWAN KYUNG - yeanie rachmawati (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTMovies as entertainment, information and education can influence thecommunity based on the message content implicit in the film. Korean drama "MiracleIn Cell no.7" is a film that tells about the struggle of a father who willingly sacrificedhimself for the happiness of his daughter. This research is a qualitative researchusing semiotic approach, especially semiotics of John Fiske which there are threelevels to analyze the object in the film that is reality level, representation level andideology level.The results of this study indicate that in the movie "Miracle In Cell No.7"there is the role of the characters who carry the message of masculinity in theanalysis through the analysis of male relationships with the social world, men withthe world of work and the relationship of men with family.Keywords: Masculinity, Film, Semiotics, John Fiske